Optimalisasi Peningkatan Kapasitas Pengetahuan Masyarakat Terhadap Bionomik dan Upaya Pengendalian Vektor Demam Berdarah Dengue - Pratiwi Hermiyanti; Ngadino; Slamet Wardoyo (Forum Kerjasama Pendidikan Tinggi, 2025)
Bohar Village is a DHF endemic village with data from the last 3 years showed an increasing number of cases. In 2020 there were 6 cases, in 2021 there were 8 cases and in 2022 there were 12 cases. The incidence of DHF cases is actually found more in residential locations. Indications that people who do not know the bionomics/behavior of the Aedes mosquito vector and inappropriate control methods make DHF cases still occured in Bohar Village. Efforts are needed from the village government and the cooperation of local health facilities to establish larva monitors and improve their knowledge in controlling vectors so that dengue cases can be controlled. The purpose of this activity is to provide counseling to larva monitors related to bionomics and efforts to control DHF vectors. Methods of counseling on bionomics and mosquito habits as well as mosquito larvae control practices were used in this community service. The targets of community service are people who have been appointed by the Bohar Village government to become larva monitors. In the implementation of community service, the targets followed enthusiastically until the event ended. The target has been able to answer questions as evidence of understanding of the material on the habitual behavior of the Aedes mosquito and its control efforts. The follow-up of this community service is an evaluation of the effectiveness of vector control on the incidence of dengue cases in Bohar Village.